Long-Lasting Hyperalgesia Is Common in Patients Following Patella Fractures. Issue 3 (17th June 2017) - Larsen, Peter; Vedel, Julie Odgaard; Vistrup, Sabina; Elsoe, Rasmus
Abstract: Background: The objective was to investigate the long-term development of pain and hyperalgesia after patella fractures. The secondary objective was to report the association between tibiofemoral and patellofemoral osteoarthritis, pain, and hyperalgesia. Methods: The study used a cohort design. Patients who were treated for patella fractures between January 2006 and December 2009 were identified. Patients age 20 to 78 years were included. The main outcome was the pain pressure threshold (PPT). Moreover, visual analog scale (VAS) for pain, radiological outcomes of patellofemoral and tibiofemoral osteoarthritis, and the pain subscale of the WOMAC and EQ-5D questionnaires were used. Results: Forty-nine patients were included, with a mean age of 53.9 years and a mean follow-up time of 8.5 years. The injured knee region showed significantly decreased PPT levels ( P  < 0.046), but decreases in PPT were not found for the forearm region ( P  = 0.24). The VAS score for the worst pain during the last 24 hours was reported, with a mean of 2.9 ± 2.4 cm. The EQ-5D-5L-pain scale was reported, with a mean score of 2.4 (95% confidence interval [CI] = 2.0–2.7). The WOMAC Pain score was reported, with a mean score of 3.9 (95% CI = 2.8–4.9). Moderate correlations were found between the VAS scores and PPT levels (R = 0.428, P  = 0.002). Weak correlations were found between VAS scores and PPT levels for site 7 (forearm; R = 0.313, P  = 0.03). Conclusions: The present study suggests that long-lasting local hyperalgesia following a patella fracture is common. No side-to-side difference at the forearms were observed, indicating that the observed local hyperalgesia was not part of a generalized sensitization.